Explicating perceived sustainability-related climate: A situational motivator of pro-environmental behavior - LEUNG, Yan Wah (Institutional Knowledge at Singapore Management University, 2019)
Individuals take cues from their surroundings when deciding whether to perform pro-environmental behaviors. Previous studies have acknowledged the role of structural, policy, and communication efforts to encourage pro-environmental behavior. Such studies demonstrate the importance of evaluating the external contexts when examining behaviors. Yet, there is a lack of explication of what external context is entailed. Expanding the concept of perceived sustainability-related climate (PSRC) used in organizational communication literature, this study proposes two dimensions that shape PSRC in the workplace—structural cues and social cues. The study then generalizes PSRC such that it is applicable in contexts beyond the workplace and proposes a 10-item scale to measure PSRC. Using confirmatory factor analysis, this study tests the factor structure and concurrent validity of the concept. The study also tests convergent validity of PSRC with social norms, perceived behavioral control, and attitudes.